AN ANALYTICAL VIEW OF THE USES AND ABUSES OF SOCIAL MEDIA IN THE LIGHT OF ISLAMIC PERSPECTIVE - Dr Razia Shabana; Dr.Tahmina Fazil; Dr. Muhammaad Zafar Iqbal Saeedi; Lubna Qasim; Amna Bibi; Sadia Riaz; Fatima Javed; Naseem Akhtar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
Islamic teachings are not against to the modern inventions, also not against to the development of scientific methodology. Islam and modern inventions are considered to separate fields and Islamic scholars condemned some inventions of science and scientists also condemned some faiths of Islamic beliefs. This debate has its own background and context. It is truly fact that Islam is a religion of future. The creations of modern age are not bad if they are in the best interest of the humanity. Similarly in these days media is playing a vital role in the world. We are able to get the things, information in every field of life through using the media. Now a days social media platforms and its need has own importance. Politic or business, entertainment or games, economics or social, educational or vocational, preachers or motivators, writers and philosophers are advertising their respective works by social media. The importance of media is shown that there is no colorful and charming life without the use of social media. In this world we are not able to live in isolation Contact to other people for knowing their cultural and socio position is possible through media. In this article we will try to analysis the uses and abuses of media and will try justify the current situation in the light of Islamic literature because Islam is a name of that quality which provides equal rights and opportunities for everyone. It is a special quality of Islamic literature. Then we will try to promote those things which are according to Islamic teachings and will try to overcome which are not according to Islamic teaching.